2021
DOI: 10.3390/cancers13163962
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Treatment Strategies among Women with Low-Risk DCIS and Oncologists

Abstract: As ongoing trials study the safety of an active surveillance strategy for low-risk ductal carcinoma in situ (DCIS), there is a need to explain why particular choices regarding treatment strategies are made by eligible women as well as their oncologists, what factors enter the decision process, and how much each factor affects their choice. To measure preferences for treatment and surveillance strategies, women with newly-diagnosed, primary low-risk DCIS enrolled in the Dutch CONTROL DCIS Registration and LORD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Women understood and were generally accepting of active monitoring being an option for low-risk DCIS, in particular due to the low-risk nature of the condition and the ongoing monitoring to pick up any changes. Parallel views have been found in recent studies on DCIS and low-risk thyroid cancer where active monitoring was being discussed as a potential management option [15,34]. Similarly, there is evidence of increasing support for and use of active surveillance as management for low-risk prostate cancer [35,36].…”
Section: Plos Onementioning
confidence: 72%
See 1 more Smart Citation
“…Women understood and were generally accepting of active monitoring being an option for low-risk DCIS, in particular due to the low-risk nature of the condition and the ongoing monitoring to pick up any changes. Parallel views have been found in recent studies on DCIS and low-risk thyroid cancer where active monitoring was being discussed as a potential management option [15,34]. Similarly, there is evidence of increasing support for and use of active surveillance as management for low-risk prostate cancer [35,36].…”
Section: Plos Onementioning
confidence: 72%
“…These trials compare standard treatment for low-risk DCIS to active monitoring (every 6 or 12 months) to determine whether women diagnosed with low-risk DCIS can safely avoid surgery, at least until and if progression occurs. Results from these trials are expected in a few years' time, although all have faced recruitment challenges [15]. A similar trial proposed for Australia and New Zealand [16] did not gain funding to proceed.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 7 studies with a qualitative methodology 13,[29][30][31][32][33][34] and 15 studies with a quantitative methodology [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were included. The total number of participants in these studies was 3817.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…49 In contrast, women in the Netherlands assigned less importance on the future risk of a secondary BC compared to the risk of surgery. 36 Alopecia BC patients undergoing chemotherapy often reported alopecia as the most distressing and most desired to be avoided side effects. 29,47 Among those receiving taxane-based chemotherapy, madarosis had been shown to significantly impact their daily lives.…”
mentioning
confidence: 99%
“…If active surveillance replaces surgical treatment for low-risk DCIS treatment, this may further complicate the use of endocrine therapy among DCIS patients. Moreover, a study by Byng et al found that patients and providers prefer active surveillance over breast-conserving surgery and mastectomy in the treatment of low-risk DCIS [ 23 ]. Endocrine treatment preferences among patients and providers are less understood.…”
Section: Introductionmentioning
confidence: 99%